Sequência propositiva do Teorema de Pitágoras com uso do Geogebra para o 9º ano do ensino fundamental - COSTA, Alaíne Lopes (2023)
The present work guides a discussion regarding the use of digital technologies regarding the teaching and learning of Mathematics, in view of this factor, with the use of the Geogebra software, a didactic sequence of the Pythagorean Theorem was created, to be applied in a 9th grade class. year of elementary school, it is worth mentioning that this research has a propositional expository character. The purpose of carrying out this didactic sequence, since Mathematics is considered difficult by many students, is to bring a more dynamic, interactive and meaningful way for students to work with mathematical content. In this way, the dicactic sequence with the use of Geogebra can instigate the pleasure in the study of mathematical contentes, and with Regard to the contente on the Pythagorean Theorem, enhance the dynamic understanding of this theorem, Leading students to a perspective diferente from the one commonly seem in classroom, on the blackboard.